The transformation of Balinese women as agents of change in tourism village management: A social representation perspective - Dewi, Luh Gede Leli Kusuma; Indrawati, Yayu; Pratama, I Putu Andre Adi Putra (YAYASAN MITRA PERSADA NUSANTARA, 2025)
Community-based tourism in Bali places women in a central role, but social representations influenced by patriarchal structures often limit their role in strategic decision-making. This study aims to analyze the transformation of Balinese women as change agents in tourism village management. Using a qualitative-phenomenological approach, this study conducted in-depth case studies of three women leaders in the tourism villages of Tista, Klecung, and Sayan. The results show a systematic cycle of empowerment in which women actively gain access through institutional, personal, and digital channels; establish control over institutions and cultural assets; demonstrate substantive and empowering participation; and obtain multidimensional benefits (economic, social, and psychological) that are redistributed to the community. This process proves that women have successfully deconstructed old social representations and reconstructed their self-image as competent public leaders. This transformation not only contributes to the achievement of the SDGs on Gender Equality (SDG 5) and Inclusive Economic Growth (SDG 8), but also offers a model for fairer and more sustainable tourism development.